Halal animal feed in Malaysian aquaculture industry: Malaysian regulatory framework and Shariah perspective / Nurulaina Saidin - Saidin, Nurulaina (2019)
In Halal Food Supply Chain, animal feed is considered as the initial Critical Control Point in ensuring the halal integrity of animal-based food products. The uncertainties in the halalness, quality, and safety of the animal feed may consequently affect the halal and tayyiban status of the halal food products. In Malaysia, despite the existence of an established regulatory framework on animal feed, fraudulence in animal feeding practices, especially related to animal feed ingredients still continuously occur and repeatedly reported in the media. Therefore, this study provides an analysis of the legal and regulatory framework relating to animal feed and feeding in Malaysia. The Shariah perspective on this topic has also been comprehensively discussed. The central argument of the thesis is that the existing laws are inadequate to control activities related to the production and use of halal animal feed in the country. This study is carried out to analyse: First: the adequacy of the current Malaysian legal and regulatory framework to regulate activities related to halal animal feed in Malaysia, Second: the Shariah perspective of halal animal feed and feeding practices in animal production, and Third: the recommendations for improvement in the form of legal reform and other contribution to rectify the issue. To achieve these objectives, legal research methodology involving a combination of doctrinal and non-doctrinal approaches is utilised. The findings indicate that the existing Malaysian legal and regulatory framework on animal feed is regulatory in nature, but lack of provisions which provide for the control of the halal aspect of animal feed in terms of its ingredients, processing, production, sale and use. There are a few ambiguities, inadequacies, and inconsistencies in the existing legal framework that make it incapable of controlling halal feed-related activities. These findings has led to the conclusion that, in order to regulate halal feed production and use in the country, a few amendments and improvements shall be made to the Feed Act 2009 and its regulations so as to extend its jurisdiction to also include the control on the halal aspect of animal feed in term of its ingredients, production, sale and use. In addition, it is also the finding of this study that a halal standard, especially for aquaculture feed production is proposed based on the current needs of the halal food industry. Besides, few recommendations had also been suggested as references for policymakers and animal feed and livestock industry players in Malaysia.